29 Adapting Dementia and Delirium Awareness Training to a Rehabilitation Setting. (16th September 2019) - O'Brien, Emma; Devine, Monica; Maxwell, Sarah; McDonnell, Catherine; Lee, Stuart
Abstract: Background: The patient profile in a Dublin rehabilitation hospital has changed in recent years to include older adult rehabilitation alongside orthopaedic rehabilitation. A snapshot audit completed by the occupational therapy department on one day in 2018 demonstrated that 64% of patients had an assessment score indicative of a cognitive impairment. A subjective gap in knowledge regarding dementia care and a misunderstanding of the ability of people with dementia to engage in rehabilitation was identified. It was imperative that dementia awareness training was provided with a particular focus on modifying rehabilitation techniques to cater for these patients. Methods: A dementia care committee was established with an Educational Development subgroup responsible for addressing dementia and delirium awareness training. Educational material was received from the field of occupational therapy, nursing, medicine, pharmacy and dietetics. The programme was accredited by the Nursing and Midwifery Board of Ireland. A focus group was completed pre/post formulation of the presentation with various departmental representatives. Feedback provided was used to inform and finalise the training content. Results: Sessions are completed once monthly. One hundred and seven participants to date have attended. Ten-point Likert scales are completed pre and post training. Data from the Likert scales were analysed revealing on average a 24.4 % increase in knowledge of dementia, a 27.6% increase in awareness of the impact of dementia on function and a 23.3% increase in confidence in caring for a patient with dementia. Highest contingent of staff members trained were household and catering staff (19%) nursing staff (18%), and health care attendants (13%). Conclusion: This essential training is ongoing with thirty per cent of staff trained to date. The objective is for all staff to complete this training for enhanced care and rehabilitation for all patients with dementia. It will also aim to review treatment for all patients with cognitive impairment so unique rehabilitation programmes can be tailored.